Through the gates death - Fortune, Dion (York Beach, ME Weiser Books, 2000)
Death is a universal experience. No one can hope to escape. It is only a matter of time till it comes to each one of us and each one of those we love. Yet what is it that makes such a natural process so terrible? Most death beds are peaceful when the time comes, so what, then, is it we fear in death that it should be for us a thing of grief and dread?In Through the Gates of Death, Dion Fortune presents a dynamic assessment of what really happens when the soul finally separates from the physical body, revealing the knowledge that constituted the supreme degree of the Egyptian mysteries.Spiritism in the Light of Occult Science is Dion Fortune's in-depth study of a phenomenon which swept the world of her day. It covers all aspects of the subject including Communication with the Departed, the Psychology of Trance-Mediumship, The Physical and Mental Phenomena of Trance and the Dawn of the Higher Consciousness
D., 8/04
Keywords: Death--Miscellanea; Occultism